KARAKTERISTIK PENDERITA STROKE RAWAT INAP DI RSUD. SIBUHUAN KABUPATEN PADANG LAWAS TAHUN 2014-2015 - indah amani; Rasmaliah .; Jemadi . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
ABSTRACT Based on data Result of The Research Primary Health (Riskesdas) 2007, prevalence of a stroke in Indonesia found of 8,3 per 1000 population and Riskesdas 2013 prevalence of a stroke 12,1 per 1000 population. The number of cases a stroke in hospital Sibuhuan district Lawas increasing each year, about 24 the number of cases stroke cases in 2014 increased to 63 cases in 2015. It is therefore necessary research to know characteristic stroke patient in hospital’s Sibuhuan district Padang Lawas in 2014-2015. This research is descriptive with case series design, using secondary data. The population were 105 stroke patient data which registered in RSUD. Sibuhuan District Padang Lawas in 2014-2015, and sample was all the population. The research result obtained highest proportion of age 55-64 years old (41,9), male (55,2%), Mandailing etnic (91,4%), high senior school education (25,7%), farmers (51,4%), marriage (61%), hypertension (44,8%), attact onset ≤6 hours (89,5%), first attack strokes (97,1%), not yet a CT Scans (69,5%), Non haemorragic/ ischemic (68,6%), hemiparesis dextra (53,3%), length of stay ≤ 7 days (92,4%), BPJS (86,7%), referred to another hospital (53,4%), and Case Fatality Rate (CFR) stroke (15,24%). There was no difference age based risk factors (p=0,206), sex based risk factors (p=0,400), risk factors based type of stroke (p= 1,000), attact onset stroke based of stroke (p= 0,662), attact onset stroke based the paralysis (p=0,986), type of stroke based the paralysis (p=1,000), length of stay based type of stroke (p=0,998) and attact onset stroke based the state out of the hospital (p=0,871). There was difference CT Scan based type attact stroke (p=0,026) and type of stroke based the state out of the hospital (p=0,001). To stroke patient so that immediately get health services ≤6 hours arising attact if a stroke and also stroke patient who have of hypertension, cardiovascular disease and diabetes meliitus in order to check health regularly. For the hospitals should add human resources, infrastructure and recording characteristics data stroke patien based education, work and married status. Keywords : Stroke, Characterisitc of Stroke Patient, Sibuhuan Hospital